2014
DOI: 10.1177/1758736014533982
|View full text |Cite
|
Sign up to set email alerts
|

Comparative stress analysis of delayed and immediate loading of a single implant in an edentulous maxilla model

Abstract: Stress distribution in peri-implant bone in an edentulous maxilla following delayed and immediate loading implant and the effect of implant length on the maximum stress were evaluated by using two kinds of finite element analyses. A threaded implant was loaded with a 100 N vertical force, either immediately or delayed, and examined by finite element analysis with a simple contact relation or a bonding interaction between the implant and the bone, respectively. Higher stresses were observed in cortical bone aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A major advantage of this program is that the 3D FE model can be moved and parts can be added or deleted at will comparatively easily. This functionality means that MF has wide applicability, not just in the field of research but also in clinical practice [ 23 , 24 ]. Further, the program can calculate the shape and material property data needed to assess bone strength [ 15 , 19 ] from 3D X-ray CT scans, so that highly reliable results can be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of this program is that the 3D FE model can be moved and parts can be added or deleted at will comparatively easily. This functionality means that MF has wide applicability, not just in the field of research but also in clinical practice [ 23 , 24 ]. Further, the program can calculate the shape and material property data needed to assess bone strength [ 15 , 19 ] from 3D X-ray CT scans, so that highly reliable results can be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…1 This technique eliminates the necessity to wait during a healing time, permits the use of a provisional prosthesis after the implant insertion, and keeps the implants in function during healing.…”
Section: Introductionmentioning
confidence: 99%
“…The stress levels around implants used in immediate loading are dramatically higher than for delayed loading. 1 Considering that all implants are available to support a denture, the presence of overload conditions can compromise the overall osseointegration process. Therefore, the best adaptation between the implant and the prosthesis is always clinically desirable.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no evidence about whether immediate loading causes increased failure rates of short implants. Biomechanical finite element analysis revealed that an increased implant length caused a decrease in bone stresses in immediate loading models, which indicated that short dental implants under immediate loading will suffer from higher bone stresses, and this may affect the failure rates and the marginal bone level change 27 . Despite growth in the number of studies on these problems, the sample size of related studies is limited, and the findings of these studies are not completely consistent 28,29 …”
mentioning
confidence: 99%